To Study the Various Attacks and Protocols in MANET - Kaur, Harkiranpreet; Kaur, Rasneet (International Journal of Computer Sciences and Engineering, 2025)
MANET is a network which has no central coordinator and the nodes are free to move in any direction because there is no fixed infrastructure. There are various types of attacks which can easily harm the security of the network. Sender sends a packet to the destination by using the best path with the help of routing protocols. In this review paper, numerous attacks will be discussed.